Typology of patients with mental health disorders and perceived continuity of care. (3rd May 2020) - Loranger, Claudie; Bamvita, Jean-Marie; Fleury, Marie-Josée
Abstract: Background: While multiple socio-demographic, clinical and service use variables have been associated with continuity of care (CoC) in patients diagnosed with mental health disorders (MHDs), little is known about how these variables may inform clinical practice and service planning. Aim: This article identified profiles of patients with MHDs to better understand their perceptions of CoC. Method: The sample for this cross-sectional study comprised 327 patients recruited by staff or self-referred from four local health networks in Quebec (Canada). Data were collected using standardized instruments, and patient medical records. A three-factor conceptual framework based on Andersen's Behavioral Model was used, integrating predisposing, needs and enabling factors. Results: Cluster analyses identified five patient profiles. Profiles that included relatively more patients with common MHDs reported less continuity than those with patients primarily affected by severe MHDs. Conclusions: Service planning and delivery should be better adapted to patient profiles in order to improve CoC, and increased access to services prioritized.